Handbook to life in ancient Greece - Adkins, Lesley 1955-; Adkins, Roy 1951- (Facts on File, 1997)
This excellent resource covers, in broad subject areas, 3,000 years of Greek history, from the Minoan civilization of Crete to the defeat of the Greeks by the Romans in 30 b.c. Gathers information on leaders, the military, economy, industry, commerce, towns, architecture, the Greek language, Greek literature, religion, myths, art, philosophy, science, and everyday life
Keywords: Dagelijks leven; Griekse oudheid; História antiga (vida cotidiana) - Grécia antiga; Sociale geschiedenis; Alltag; Gesellschaft; GrÉcia (CivilizaÇÃo); Griechenland (Altertum); Griechenland; Greece -- Civilization; Griechenland -- Altertum